Authenticating Hadith Manuscripts and the Methodology of Textual Accuracy - Klaina, Mekki (Asian Journal of Islamic Studies and Da'wah, 2025)
This research highlights the importance of manuscript verification in general, and particularly the verification of hadith manuscripts, through the efforts of hadith scholars. It aims to achieve several objectives, including guiding graduate students on the precise methodology to follow when verifying manuscripts, and raising awareness among youth about the significant role of hadith scholars in defending Islam and preserving the Prophetic Sunnah from attacks. The research also addresses the question of whether hadith scholars had a comprehensive methodology for verifying texts and preserving manuscripts or if the Islamic heritage has been subject to distortion, as some individuals attempt to spread these ideas among the youth to cast doubt on their faith. The research method follows the exploration of the applications of hadith scholars in their writings, extracting their methodology in preserving texts, verifying manuscripts, and ensuring the accurate transmission of hadith. The study's findings indicate that the scholars relied heavily on comparing narrations and manuscripts through methods such as presentation and comparison, ensuring the reliability of narrators and copyists, and preventing scribal errors. The study concluded with a proposal to establish a center dedicated to the scientific verification of heritage, aimed at preserving the nation's history and contributing to the development of human knowledge. This is crucial to prevent being influenced by the animalistic culture promoted by those who seek to corrupt this nation. The proposal also emphasizes the need to spread noble values and sound Islamic thought, free from deviations. Furthermore, it calls for the implementation of punitive laws for university educators who promote unethical behavior.